Aplikasi Pembelajaran Manasik Haji dan Umroh Berbasis Android - Dimas Robby Firmanda; R. Rizal Isnanto; Ike Pertiwi Windasari (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2016)
There are many Muslim people who do not know the information about how to do the pilgrimage and perform a pilgrimage to Mecca that usually called ‘Hajj’ and ‘Umrah’. Hajj and Umrah are the duty of Moslem who has the ability to do that. In the mobile application, there are many advantages that can be used for learning, especially the app based Android. The purpose the research is to develop a mobile application as a learning media how to do Hajj and Umrah that is interactive for everyone through Android devices. With a guide app how to do Hajj and Umrah based Android, is expected can facilitate users to learn how to do Hajj and Umrah well and right. This application uses Android Studio software as IDE, in making the Android app. The first step to make the app is making a design like the design of the text, picture, animation, and audio about how to do Hajj and Umrah. Then, the second step is adding the basic rules of the pray in Arabic text with the meaning of that text. The third step is adding the picture, animation, and audio about the pray and the proposition into Android Studio layout with Webview, and then doing initialization by adding the sound of every praying pronunciation in every Hajj and Umrah steps. The result of making the research is a multimedia application which displays to a user about the text, picture and audio about how to do Hajj and Umrah based Android and facilitate user to learn easier.